Changes In People's Consumption Patterns In The Digital Era: A Study On The Millennial Generation - Teguh Lesmana (Nomico, 2024)
The millennial generation, born between the early 1980s and early 2000s, grew up in the era of digital technology that affects their consumption patterns. This study uses a qualitative approach with case study design, collecting data through in-depth interviews, case studies, and participatory observations, which are analyzed thematically. The results show that millennials prefer online shopping through e-commerce platforms, influenced by social media and influencers, and prioritizing experience over goods ownership. They are also sensitive to social and environmental values in choosing products. The use of mobile apps for transactions and product reviews is very dominant, although challenges related to data privacy and information reliability are major concerns. This research reveals the need for content-based marketing strategies, product and service customization, and increased transparency and data security to build consumer trust. These findings provide in-depth insights into the consumption dynamics of millennials in the digital era, offering guidance for companies to develop more adaptive and innovative strategies in the face of evolving consumption trends.